Simultaneous detection of enrofloxacin and chloramphenicol antibiotics using surface-enhanced Raman spectroscopy combined with triangular silver nanoplates - Cao, Dao Tran; Luong, Truc Quynh Ngan; Cao, Tuan Anh (Communications in Physics, 2024)
The emergence of antibiotic residues in the environment and food requires the development of sensitive and selective detection methods for monitoring these contaminants. In fact, many different types of antibiotics will be used simultaneously to prevent diseases in livestock and aquatic animals, causing antibiotic residues in food and the environment. Rapid and accurate simultaneous analysis of multiple antibiotics at low concentrations remains a major challenge in in the field of rapid detection. This study presents a sensitive and selective method for the simultaneous detection of two widely used antibiotics, enrofloxacin and chloramphenicol, by combining surface-enhanced Raman spectroscopy (SERS) with triangular silver nanoplates. Triangular silver nanoplates (TAgNPls) in the form of colloid were simply synthesized by chemical reduction method and then used as an effective SERS substrate, enhancing the Raman signals of the target antibiotics and enabling the detection of these antibiotics at trace levels. It was found that with a SERS substrate assembled from the above TAgNPls, the antibiotics enrofloxacin and chloramphenicol could be detected with detection limits of 2.6 µg/L and 4.3 µg/L, respectively. In addition, this SERS substrate also allows simultaneous detection of the above two antibiotics in one analytical sample with concentrations as low as 10 µg/L for both substances. The proposed method holds promise for addressing concerns related to antibiotic contamination in various environments and food sources, contributing to the advancement of analytical techniques for the trace detection of pharmaceutical residues.